Islamic Work Ethic and SME Performance: Evidence from Indonesia and Malaysia - Asfiah, Nurul; Febriani, Rizki; Arifiani, Ratya Shafira; Anuar, Aimi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the effect of Islamic Work Ethic (IWE) on SME business performance in Indonesia and Malaysia through Innovative Work Behavior (IWB) and Islamic Social Entrepreneurship (ISE). The study advances the literature by demonstrating that Islamic ethical values influence firm performance through behavioral and entrepreneurial mechanisms rather than direct moral orientation alone. Using a quantitative explanatory design, data were collected from more than 300 SME owners in 2024 and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that IWE significantly enhances innovative work behavior and Islamic social entrepreneurship, both of which positively influence business performance, with innovative work behavior partially mediating the relationship. These findings indicate that embedding Islamic ethical principles in entrepreneurial practices strengthens innovation capacity and value creation, offering strategic guidance for SMEs seeking sustainable performance in Muslim-majority economies.